The effects of non-digital game-based learning and cognitive level of questions on isometric transformations / Shamsurya Hamden Hamid, Norehan Zulkiply and Fitri Suraya Mohamad - Hamid, Shamsurya Hamden; Zulkiply, Norehan; Mohamad, Fitri Suraya (Universiti Teknologi MARA, 2022)
The present study examined the effects of the non-digital game-based instructional method and the cognitive level of questions in determining students’ achievement in mathematics, particularly in Isometric Transformation. The study used a quasi-experimental design and involved 116 participants (i.e., form two students) from two local secondary schools in Kuching. The participants were divided into control and experimental groups – the control group learned the Isometric Transformation topic via conventional learning, while the experimental group used non-digital game-based learning (NDGBL). The results showed that participants who learned using the NDGBL scored better in the Isometric Transformation test than those who learned the topic using the conventional instructional method. The present findings also showed that participants’ achievement of Isometric Transformation differed significantly between cognitive levels of questions. In particular, participants’ achievements were recorded better for lower-level cognitive questions than higher-level cognitive questions. However, there was no significant interaction effect between the instructional method and the cognitive levels of questions on participants’ achievement in the topic learned. The study provided empirical evidence on the role of NDGBL in learning Isometric Transformation, in that it should be considered as an alternative approach for learning Isometric Transformation and Mathematics in general, with an effective integration into the secondary mathematics curriculum.